Dermeval Saviani : professor intelectual - Almeida, Claudia de Carvalho Cosmo (2015)
This work has as its theme the life and academic career of Dermeval Saviani and their contributions to the educational debate in Brazil, from the consideration that he became an intellectual proponent. He’s graduated in Philosophy from the Pontifical Catholic University of São Paulo (PUC-SP), where he also received his doctorate; Saviani is now professor emeritus at the State University of Campinas (UNICAMP). The research is justified by the many legacies that Dermeval Saviani brings to the Brazilian education, which are present in teaching and research, including an extensive publication in the areas of Philosophy of Education, Educational Law and History of Education. The objectives of this research are: to highlight the key moments of life and academic career of Dermeval Saviani, linking these events to the historical context, its research and production as well as the development process of the postgraduate studies in Education in Brazil; to discuss the concepts of ‘System’, ‘Educational Work’ and ‘Social Practice’ in the Dermeval Saviani’s work and which is his conception of ‘Education’ and ‘School’; to reflect about the role and contributions of Dermeval Saviani in the educational debate in Brazil, including his role in the organization of study and research groups, its proposal for a preliminary draft bill of Directives and Bases of National Education Law in the 1980s, just like the Historical-Critical Pedagogy’s perspective; to understand the Saviani’s role as intellectual proponent and organizer of the research field of the Brazilian History of Education. For the sources to deal with biographical and institutional aspects, we resort to autobiographical texts and authors who lived with Demerval Saviani ones, whether on condition of workmates and students, both as students and supervised by him. To address the above concepts, the sources are their own works. Regarding the methodological approach, we use the following categories: historicity, totality and contradiction and the following concepts: political culture, networks and/or elementary structures of sociability and solidarity of age, generation and study — important elements for the study the history of intellectuals. We consider that Dermeval Saviani, for its history, surpassed the teacher, researcher and author characteristics, constituting himself as intellectual, as evidenced by their engagement and the socially recognized function that he performs linked to scientific and philosophical spheres and educational-cultural and policy ones.